Study of Sedimentation Control on Bangga River, Palu Watershed, Central Sulawesi - Savitri, Fanny Aliza; Bagus Adityawan , Mohammad; Widyaningtias, Widyaningtias (Institut Teknologi Bandung, 2023)
Abstract. Bangga River is located in a mountainous area in the Palu River Basin with an area of 74.82 km2 and a river lengthof 16.97 km. Flood with the approximated water depth of 3 m occur in Bangga’s Village. The cliffs upstream of theBangga River areunstable and can easily collapse due to the disaster. Ministry of Public Works and Housingcontrol through Sabo dam’s structure. This study aims to analyze the performance of sabo dam’s structure inreducing sediments and the floods. Analysis and modeling using two scenarios, before and after the sabo damstructure’s control was built, using HEC-RAS Software with purposeful 1D modeling to simulate flow patterns, totalsediment. The HEC-RAS simulation shows that the water surface is stood at 2.1 m depth in the existing condition.Sabo dam structure can reduce of sediment transport, which was computed according to Engelund (81%reduction), Mayer Peter Muller (MPM) with 92% reduction, and Yang (91% sediment yields reduction). So, thesabo dam's structure is not merely utilized to retain the sediment, but it can reduce potential flooding in the future.Keywords: Sedimentation, sediment control building, HEC-RAS, sabo dam, flood. Abstrak. Sungai Bangga terletak di daerah pegunungan di DAS Palu dengan luas 74,82 km2 dan memiliki panjang sungai16,97 km. Banjir dengan kedalaman air + 3 m terjadi di Desa Bangga. Tebing-tebing di hulu Sungai Bangga tidakstabil dan mudah runtuh akibat bencana. Kementerian Pekerjaan Umum dan Perumahan Rakyat mengontrolmelalui bangunan Sabo dam. Penelitian ini bertujuan untuk menganalisis kinerja bangunan Sabo dam dalammereduksi sedimen dan banjir. Analisis dan pemodelan dilakukan dengan dua skenario yaitu sebelum dan sesudahbangunan sabo dam terbangun, menggunakan Software HEC-RAS dengan pemodelan 1D yang bertujuan untukmensimulasikan pola aliran dan total sedimen. Simulasi HEC-RAS menunjukkan bahwa kedalaman air beradapada 2,1 m pada kondisi eksisting. Bangunan sabo dam dapat mereduksi transpor sedimen, yang dihitung menurutbeberap rumus yaitu Engelund (reduksi 81%), Mayer Peter Muller (MPM) dengan reduksi 92%, dan Yang (reduksi91%). Jadi, bangunan sabo dam tidak hanya dimanfaatkan untuk menahan sedimen, tetapi dapat mengurangipotensi banjir di masa depan. Kata-kata kunci: Sedimentasi, bangunan pengontrol sedimen, HEC-RAS, sabo dam, banjir.